2016 IEEE International Conference on Robotics and Automation (ICRA) 2016
DOI: 10.1109/icra.2016.7487475
|View full text |Cite
|
Sign up to set email alerts
|

Angled sensor configuration capable of measuring tri-axial forces for pHRI

Abstract: This paper presents a new configuration for single axis tactile sensor arrays molded in rubber to enable tri-axial force measurement. The configuration requires the sensing axis of each sensor in the array to be rotated out of alignment with respect to external forces. This angled sensor array measures shear forces along axes in a way that is different to a planar sensor array. Three sensors using the angled configuration (22.5°, 45° and 67.5°) and a fourth sensor using the planar configuration (0°) have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The grasp detection mechanism that uses the capacitive touch buttons does not allow closed loop control on the haptic feedback and modulating the output based on the detected grasp does not guarantee precise haptic output, allowing the learners to release the robots and follow their motion which is due to the motor outputs intended for haptic feedback. To mitigate these problems, we are investigating force/torque sensors to be installed on the outer shell of the robot; [31] is a promising candidate for this purpose. In addition, the user study was conducted with a limited number of participants, and more could allow us to obtain clearer results on learning gains.…”
Section: Discussionmentioning
confidence: 99%
“…The grasp detection mechanism that uses the capacitive touch buttons does not allow closed loop control on the haptic feedback and modulating the output based on the detected grasp does not guarantee precise haptic output, allowing the learners to release the robots and follow their motion which is due to the motor outputs intended for haptic feedback. To mitigate these problems, we are investigating force/torque sensors to be installed on the outer shell of the robot; [31] is a promising candidate for this purpose. In addition, the user study was conducted with a limited number of participants, and more could allow us to obtain clearer results on learning gains.…”
Section: Discussionmentioning
confidence: 99%
“…Their accuracy is significantly impacted by the orientation of the sensor. In [20], it was found that placing the sensor at a 45°angle with respect to the contact pad yields the best results. A minimal RMSE of 1.74 N was found for the normal force.…”
Section: Related Work a Tactile Sensorsmentioning
confidence: 99%
“…We use Takktile from Right Hand Robotics [6] as the sensing elements in our tactile dome. While these sensors are mainly designed to measure normal forces, Reeks et al [7] has shown that positioning these sensors at an angle can produce meaningful signals to measure shear forces. In contrast, our work focuses on contact localization over a three dimensional surface and does not provide force measurements.…”
Section: Related Workmentioning
confidence: 99%